Dynamic mechano-regulation of myoblast cells on supramolecular hydrogels cross-linked by reversible host-guest interactions - Hörning, Marcel; Linke, Philipp; Veschgini, Mariam; Kaufmann, Stefan; Tanaka, Motomu (Scientific reports, 2017)
A new class of supramolecular hydrogels, cross-linked by host-guest interactions between β-cyclodextrin (βCD) and adamantane, were designed for the dynamic regulation of cell-substrate interactions. The initial substrate elasticity can be optimized by selecting the molar fraction of host- and guest monomers for the target cells. Moreover, owing to the reversible nature of host-guest interactions, the magnitude of softening and stiffening of the substrate can be modulated by varying the concentrations of free, competing host molecules (βCD) in solutions. By changing the substrate elasticity at a desired time point, it is possible to switch the micromechanical environments of cells. We demonstrated that the Young’s modulus of our “host-guest gels”, 4-11 kPa, lies in an optimal range not only for static (ex situ) but also for dynamic (in situ) regulation of cell morphology and cytoskeletal ordering of myoblasts. Compared to other stimulus-responsive materials that can either change the elasticity only in one direction or rely on less biocompatible stimuli such as UV light and temperature change, our supramolecular hydrogel enables to reversibly apply mechanical cues to various cell types in vitro without interfering cell viability.